2021
DOI: 10.1186/s12969-021-00571-9
|View full text |Cite|
|
Sign up to set email alerts
|

Juvenile idiopathic arthritis in Harlequin ichthyosis, a rare combination or the clinical spectrum of the disease? Report of a child treated with etanercept and review of the literature

Abstract: Background Harlequin ichthyosis (HI) is the most severe phenotype of autosomal recessive congenital ichthyosis. Juvenile Idiopathic Arthritis (JIA) represents a heterogenous group of disorders all sharing the clinical manifestation of chronic arthritis. Association of HI and chronic arthritis has been reported in few cases. Case presentation We report the case of a child with HI who developed a severe form of chronic polyarthritis during the first … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As the highest doses do not exceed 1 mg/kg/day, its short plasma half-life minimizes negative effects (Zaenglein et al, 2021). Immune system inhibitors such as Etanercept (TNFalpha Inhibitors) have no adverse effects when used to treat juvenile idiopathic arthritis and Harlequin ichthyosis in children (Baldo et al, 2021). On the other hand, studies indicated that Adalimumab is also used to treat Ichthyosis in children; it targets the cytokine TNF-alpha, which is linked to inflammation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the highest doses do not exceed 1 mg/kg/day, its short plasma half-life minimizes negative effects (Zaenglein et al, 2021). Immune system inhibitors such as Etanercept (TNFalpha Inhibitors) have no adverse effects when used to treat juvenile idiopathic arthritis and Harlequin ichthyosis in children (Baldo et al, 2021). On the other hand, studies indicated that Adalimumab is also used to treat Ichthyosis in children; it targets the cytokine TNF-alpha, which is linked to inflammation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The harlequin ichthyosis, the extreme impairment in premature terminal cornification process [due to mutations in the adenosine triphosphate (ATP)-binding cassette, subfamily A member 12 (ABCA12) gene], manifests as a rough, rigid cuirass of hyperkeratosis, spaced by profound crevices; it is a syndrome that presents itself in association with nose and ears malformations, important eclabium and ectropion and, recently reported, severe involvement of both large and small joints with a chronic progression [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Th-17/IL-23 polarization has been found in some ichthyoses [ 244 ]. Th17 cells play also a pathogenetic role in juvenile idiopathic arthritis [ 245 ]. It is therefore of note that Auriti et al [ 246 ] described 2 patients with Harlequin ichthyosis who developed juvenile idiopathic arthritis [ 247 ] that has an incidence of 15–150/100.000 in the first 2 years of life.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore of note that Auriti et al [ 246 ] described 2 patients with Harlequin ichthyosis who developed juvenile idiopathic arthritis [ 247 ] that has an incidence of 15–150/100.000 in the first 2 years of life. The observation of an association between these rare diseases [ 245 ] highlights that clinicians should be aware of onset of juvenile idiopathic arthritis in patients with Harlequin ichthyosis and promptly identify it. Furthermore, additional understandings on the pathophysiology of the relationship between the two diseases may elucidated whether novel treatments such as IL-17 targeting drugs, may be of benefit.…”
Section: Introductionmentioning
confidence: 99%